Information technology capabilities and organizational agility: The mediating effects of open innovation capabilities. Issue 2 (15th July 2019) - Cepeda, Juan; Arias-Pérez, José
Abstract : Purpose: Currently, it is commonly accepted that information technology capabilities (ITC) positively influence organizational agility. Nevertheless, studies have recently started to demonstrate that different organizational factors mediate this relation under the controvertible assumption that companies are capable of responding quickly to market changes using their IT in combination with other internal resources. Therefore, companies have given very little attention to collaborative work with external partners. The purpose of this study is to analyze the mediating effects of the acquisition and exploitation capabilities of open innovation on the information technology capabilities – organizational agility relationship. Design/methodology/approach: Structural equation modeling was used to test the proposed model with survey data from a multinational corporation that operates in South American emerging economies in the pension and savings businesses. Findings: This study found that only the open innovation capability of exploitation has a partial mediating effect. This means that this organizational ability serves as a bridge so that IT capabilities can have a positive incidence on organizational agility. Originality/value: This paper adopts a more novel study focus that emphasizes the importance of collaborative work and of the use of external resources that are implicit in open innovation capability. On the other hand, this organizational ability implies external embeddedness, which is usually approached mainly from the network theory in the international business literature; however, this study offers a more interesting study focus in which externally oriented organizational abilities such as open innovation are more important for external embeddedness than are the size and quality of the external network.